Molecular Mechanism of Gelsemium elegans (Gardner and Champ.) Benth. Against Neuropathic Pain Based on Network Pharmacology and Experimental Evidence - Que, Wancai; Wu, Zhaoyang; Chen, Maohua; Zhang, Binqing; You, Chuihuai; Lin, Hailing; Zhao, Zhichang; Liu, Maobai; Qiu, Hongqiang; Cheng, Yu (Frontiers in Pharmacology, 2022)
Gelsemium elegans (Gardner & Champ.) Benth. [Gelsemiaceae] (GEB) is a toxic plant indigenous to Southeast Asia and China, which has long been used as Chinese folk medicine for the treatment of various types of pain, including neuropathic pain (NPP). Nevertheless, limited data are available on the understanding of the interactions between ingredients-targets-pathways. The present study integrated network pharmacology and experimental evidence to decipher molecular mechanisms of GEB against NPP. The candidate ingredients of GEB were collected from the published literature and online databases. Potentially active targets of GEB were predicted using the SwissTargetPrediction database. NPP-associated targets were retrieved from from GeneCards, Therapeutic Target Database, and DrugBank. Then the protein-protein interaction network was constructed. The DAVID database was applied to Gene Ontology and Kyoto Encyclopedia of Genes and Genome pathway enrichment analysis. Molecular docking was employed to validate the interaction between ingredients and targets. Subsequently, a 50 ns molecular dynamics simulation was performed to analyze the conformational stability of the protein-ligand complex. Furthermore, the potential anti-NPP mechanisms of GEB were evaluated in the rat chronic constriction injury model. A total of 47 alkaloids and 52 core targets were successfully identified for GEB in the treatment of NPP. Functional enrichment analysis showed that GEB was mainly involved in phosphorylation reactions and nitric oxide synthesis processes. It also participated in 73 pathways in the pathogenesis of NPP, including the neuroactive ligand-receptor interaction signaling pathway, calcium signaling pathway, and MAPK signaling pathway. 11-Hydroxyrankinidin matched the active pockets of crucial targets well, such as EGFR, JAK1, and AKT1. The 11-hydroxyrankinidin-EGFR complex was stable throughout the entire molecular dynamics simulation. Further experimental results demonstrated that koumine could upregulate the protein expression of EGFR and JAK1 to achieve the anti-NPP action. These findings revealed the complex network relationship of GEB in the "multi-ingredient, multi-target, multi-pathway" mode, and explained the synergistic regulatory effect of each complex ingredient of GEB based on the holistic view of traditional Chinese medicine, which would provide a scientific approach and strategy for the further studies of GEB in the treatment of NPP in the future.